On fundamental group of Riemannian manifolds with ommited fractal subsets - Mirzaie, R. (Український математичний журнал, 2011)
We show that if K is a closed and bounded subset of a Riemannian manifold M of dimension m>3, and the fractal dimension of K is less than m−3, then the fundamental groups of M and M−K are isomorphic.